Formation of organizational development strategy of enterprise in context of changes in international environment - Parkhomenko, Nataliia (Management and Entrepreneurship: Trends of Development, 2022)
The strategy of organizational development of the enterprise provides on the basis of the analysis of internal possibilities of the enterprise and an estimation of changes of the international environment of formation of a trajectory of development which provides adaptation to operating conditions; integration of divisions and business processes to achieve development indicators, substantiation of effective organizational structure, choice of organizational and legal form of business, optimization of business processes, interaction of the enterprise with components of the international environment. The aim of the study is to improve the methodological approach to the formation of organizational development strategy of the enterprise in the context of changes in the international environment based on assessing the current state of the enterprise and strategic guidelines for its development. Methodical tools are presented by methods of analysis and synthesis, comparison, matrix method, and generalization. The study formed a procedure for developing a strategy for organizational development of the enterprise, which consists of five consecutive actions. Based on the comparison of organizational development strategies, alternative strategic ways of development were formed. The matrix of choice of strategy of organizational development of the enterprise in the context of changes of the international environment which provides a choice of a direction of realization of the chosen trajectory of development was offered. The scientific significance of the study is to improve the methodological approach to the formation of organizational development strategy of the enterprise. Recommendations for developing an organizational development strategy in the context of changes in the international environment are of practical importance.JEL Classification F23, L1, L22, M16